The role of colonization with resistant Gram-negative bacteria in the treatment of febrile neutropenia after stem cell transplantation - Sokolová, T; Paterová, P; Zavřelová, A; Víšek, B; Žák, P; Radocha, J (The Journal of hospital infection, 2024)
BACKGROUND: Febrile neutropenia (FN) is a common complication of stem cell transplantation. AIM: To evaluate the frequency of sepsis in patients with FN colonized with resistant Gram-negative bacteria (extended-spectrum β-lactamase (ESBL)-positive, multidrug-resistant (MDR) Pseudomonas aeruginosa) and the choice of primary antibiotic in colonized patients. METHODS: This retrospective study analysed data from patients undergoing haematopoietic stem cell transplantation from January 2018 to September 2022. Data were extracted from the hospital information system. FINDINGS: Carbapenem as the primary antibiotic of choice was chosen in 10.9% of non-colonized +/-AmpC patients, 31.5% of ESBL+ patients, and 0% of MDR P. aeruginosa patients. Patients with FN and MDR P. aeruginosa colonization had a high prevalence of sepsis (namely 100%, P = 0.0197). The spectrum of sepsis appeared to be different, with Gram-negative bacilli predominating in the ESBL+ group (OR: 5.39; 95% CI: 1.55-18.76; P = 0.0123). Colonizer sepsis was present in 100% of sepsis with MDR P. aeruginosa colonization (P = 0.002), all in allogeneic transplantation (P = 0.0003), with a mortality rate of 33.3% (P = 0.0384). The incidence of sepsis in patients with ESBL+ colonization was 25.9% (P = 0.0197), with colonizer sepsis in 50% of sepsis cases (P = 0.0002), most in allogeneic transplantation (P = 0.0003). CONCLUSION: The results show a significant risk of sepsis in FN with MDR P. aeruginosa colonization, a condition almost exclusively caused by the colonizer. At the same time, a higher risk of Gram-negative sepsis has been demonstrated in patients colonized with ESBL+ bacteria.
Keywords: dospělí; Stem cell transplantation; Gram-Negative Bacterial Infections; Female; Adult; Febrile Neutropenia; mladý dospělý; ženské pohlaví; Adolescent; sepse; Sepsis; Multidrug resistant; Carrier State; lidé; Gram-Negative Bacteria; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; gramnegativní bakteriální infekce; Anti-Bacterial Agents; febrilní neutropenie; retrospektivní studie; gramnegativní bakterie; přenašečství; Male; Aged; ESBL positive; Young Adult; mnohočetná bakteriální léková rezistence; Febrile neutropenia; Drug Resistance, Multiple, Bacterial; lidé středního věku; senioři; mužské pohlaví; antibakteriální látky; Retrospective Studies; Middle Aged; mladiství; Humans